Revisiting cosmic acceleration with DESI BAO - Jincheng Wang; Hongwei Yu; Puxun Wu (European Physical Journal C: Particles and Fields)
Abstract We revisit the evolution of cosmic acceleration in a spatially flat $$w_0w_a$$ w 0 w a CDM universe, in which the equation of state of dark energy takes the CPL parametrization, using the latest baryon acoustic oscillation (BAO) measurements from the Dark Energy Spectroscopic Instrument (DESI), in combination with Planck cosmic microwave background (CMB) data and several type Ia supernova datasets, including PantheonPlus, Union3, and DESY5. We analyze the deceleration parameter q(z) and the jerk parameter j(z) and further validate our results using the Om(z) diagnostic. Our findings indicate significant deviations from the predictions of the $$Λ $$ Λ CDM model. Specifically, DESI BAO, DESI BAO + CMB, DESI BAO + CMB + Union3, and DESI BAO + CMB + DESY5 all provide strong evidence for a slowing down of cosmic acceleration at late times, as indicated by $$j(0) < 0$$ j ( 0 ) < 0 at more than 1 $$σ $$ σ confidence level, within the framework of $$w_0w_a$$ w 0 w a CDM model. These results suggest that in the $$w_0w_a$$ w 0 w a CDM universe cosmic acceleration has already peaked and is now in a phase of decline.